A survey on the use of library resources, services and facilities: a case study at the Faculty of Medicine and Health Science, Universiti Putra Malaysia/ Mohd Dasuki Sahak and Mohd Sharif Mohd Saad - Sahak, Mohd Dasuki; Mohd Saad, Mohd Sharif (Fakulti of Information Management, Universiti Teknologi MARA, 2011)
This study investigates the usage of library resources, services and facilities among first and third year medical students in the Faculty of Medicine and Health Sciences (FPSK), Universiti Putra Malaysia UPM. The study attempts to identify the usage of library services, resources and facilities. Questionnaire employed in this study was based on the previous works that measures the frequency of usage of library resources, services and facilities in the library by daily, weekly, monthly, once per semester or never. With regards to the library usage all respondents, 205(100%) claimed that they visited the library to study and use the Internet. They also frequented the library to do their assignments 199 (97.1%); discussions with friends 176 (85.9%) and for leisure reading 192(93. 7%). For resources, the Internet was rank first, second the newspaper, and the third are library websites. This is followed by library online database, dictionaries, handbooks and textbooks. The less frequently used resources are library OPAC, project paper, EZ-Proxy, Full text journal, encyclopedia, thesis and statistical reports. For frequency usage of library facilities the computer is rank first, followed by the reading area. The third is facilities which include discussion room, then the rest such as prayer room, printing, photocopy and self check machine.